Fluorination Enables Tunable Molecular Interaction and Photovoltaic Performance in Non-Fullerene Solar Cells Based on Ester-Substituted Polythiophene - Liang, Ziqi; Gao, Mengyuan; Zhang, Bo; Wu, Junjiang; Peng, Zhongxiang; Li, Miaomiao; Ye, Long; Geng, Yanhou (Frontiers in Chemistry, 2021)
Owing to the advantages of low synthetic cost and high scalability of synthesis, polythiophene and its derivatives (PTs) have been of interest in the community of organic photovoltaics (OPVs). Nevertheless, the typical efficiency of PT based photovoltaic devices reported so far is much lower than those of the prevailing push-pull type conjugated polymer donors. Recent studies have underscored that the excessively low miscibility between PT and nonfullerene acceptor is the major reason accounting for the unfavorable active layer morphology and the inferior performance of OPVs based on a well-known PT, namely PDCBT-Cl and a non-halogenated nonfullerene acceptor IDIC. How to manipulate the miscibility between PT and acceptor molecule is important for further improving the device efficiency of this class of potentially low-cost blend systems. In this study, we introduced different numbers of F atoms to the end groups of IDIC to tune the intermolecular interaction of the hypo-miscible blend system (PDCBT-Cl:IDIC). Based on calorimetric, microscopic, and scattering characterizations, a clear relationship between the number of F atoms, miscibility, and device performance was established. With the increased number of F atoms in IDIC, the resulting acceptors exhibited enhanced miscibility with PDCBT-Cl, and the domain sizes of the blend films were reduced substantially. As a result, distinctively different photovoltaic performances were achieved for these blend systems. This study demonstrates that varying the number of F atoms in the acceptors is a feasible way to manipulate the molecular interaction and the film morphology toward high-performance polythiophene:nonfullerene based OPVs.